Preparation and Structure of New Oxyfluoride Glass‐Ceramics Containing BaLiF3 Nanocrystal. Issue 9 (18th July 2016) - Lin, Changgui; Li, Legang; Bocker, Christian; Rüssel, Christian
Abstract : Through a careful composition design, new oxyfluoride glass‐ceramics (GCs) containing BaLiF3 nanocrystals with sizes of around 30 nm were prepared. Microstructural characterizations show interpenetrating phase separation in the sample with a composition of 15BaF2 –15ZnF2 –70SiO2, after thermal treatment at 580°C for 40 h which leads to the nanocrystallization of BaLiF3 . The BaLiF3 nanocrystals embedded in the glassy matrix could provide Ba or Li sites for the incorporation of optically active rare earth and transition‐metal ions, which provides a possibility to explore novel photonic properties by the codoping of rare earth and transition‐metal ions in GC materials.